The Induction and Evaluation of Productive Semidwarf Mutants of Basmati-370 - Sajjad, M. Siddique; Awan, M. A (1988)
Dry, uniform seeds of Basmati 370 with about 14% moisture content were exposed to 0, 15,20 and 25kR doses of gamma rays (60Co source). Twenty one semi-dwarf mutants were selected from 36,000 M2 plants originating from about 12,000 Ml plants. The breeding behaviour of these mutants was studied in M3 and consequently 6 mutants were selected. The comparative yield test of mutants with mother cultivar Basmati-370, established the high yield potential and semi-dwarf plant posture of mutant strains. The other plant attributes as well as physico-chemical traits of the mutants and parent cultivar are also presented.